Perbedaan Emotional Abuse pada Remaja Akhir yang Berpacaran Berdasarkan Pola Komunikasi dalam Keluarga - Pemayun, Cokorda Istri Indraswari; Widiasavitri, Putu Nugrahaeni (Jurnal Psikologi Udayana; Vol 2 No 2 (2015)DO - 10.24843/JPU.2015.v02.i02.p18, 2015)
Problems in dating relationship may lead to violence such as emotional abuse that usually can lead to physical abuse and sexual abuse. The need for the role of parents in control and give examples of behaviour to adolescents directly or indirectly. Children will bring exemplified parents into the social environment as communication patterns. Family communication patterns is divided into four, namely Pluralistic, Consensual, Laissez-Faire, and Protective. Communication patterns are different in every family will indirectly establish a different personality for each adolescents. Based on the exposure, this study has the objective to determine differences in emotional abuse in adolescents who are dating is based on communication patterns within the family. Subjects in this study were 75 people late adolescents who are dating and live with parents at Udayana University. Instruments in this research is the Emotional Abuse scale and Revised Family Communication Pattern (RFCP) scale. One Way ANOVA analysis results showed p=0,031 (F=3,138; p<0,05) can thus be noted that there are differences in emotional abuse in adolescents who are dating is based on communication patterns within the family. Differences are also evident from the pattern of Pluralistic group communication and Laissez-Faire contained probability value p=0,043 (p<0,05), which means that Ho is rejected or there is a difference between communication patterns within the family group pluralistic and Laissez-Faire. Adolescents who grew up with communication patterns Laissez-Faire has a higher tendency to do emotional abuse in couples than adolescents who grew up with pluralistic communication patterns.   Keywords: emotional abuse, family communication pattern, late adolescents, RFCP, Pluralistic, Consensual, Laissez-Faire, Protective